KAJIAN KUALITAS BISKUIT JAGUNG (The Study of Quality Assessment On Corn Cookies) (Jurnal Teknologi Pangan, 2015)
Abstract Biscuit is a type of baked snacks made of soft dough containing high fat, crisp and when broken fragment of less dense-textured cross section. Wheat flour is the base material of the manufacture of biscuits, to reduce the dependence of wheat flour and add to the content of vitamin A as well as food biodiversity need the addition of other flours, such as corn flour, but with the addition of corn flour biscuits will be hard so need the addition of margarine to improve crispness on the biscuits. This research aims to know the influence of proportion of wheat flour: cornmeal and addition of margarine for the physical, chemical and organoleptik biscuits. This study used a Randomized Complete Design factorial pattern consisting of 2 factors with 2 times replications, the first factor is the proportion of wheat flour: cornmeal (25: 75; 50: 50; 75: 25)% and the second factor is addition of margarine (100; 115; 130)%.The results showed that the best treatment is the proportion of wheat flour: cornmeal (25: 75)% and the addition of margarine 130%, which produce corn biscuits with moisture content = 3,780%, fat content = 37,270%, crude fibre content = 3,480%, texture = 0,666 mm/gramsecond and organoleptic flavor 5.45/like, color 5.45/like/kinda like 5.15 texture.   Keyword : biscuit, corn flour, wheat flour, margarine   Abstrak Biskuit merupakan jenis makanan ringan yang dipanggang yang terbuat dari adonan lunak yang berkadar lemak tinggi, renyah dan bila dipatahkan penampang potongannya bertekstur kurang padat. Tepung terigu merupakan bahan dasar dari pembuatan biskuit, untuk mengurangi ketergantungan terhadap tepung terigu dan menambah kandungan vitamin A serta penganekaragaman pangan perlu penambahan tepung lain, misalnya tepung jagung, tetapi dengan adanya penambahan tepung jagung biskuit akan menjadi keras sehingga perlu penambahan margarine untuk meningkatkan kerenyahan pada biskuit.Penelitian ini bertujuan untuk mengetahui pengaruh proporsi tepung terigu:tepung jagung dan penambahan margarine terhadap sifat fisik, kimia dan organoleptik biskuit.Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) pola faktorial yang terdiri dari 2 faktor dengan 2 kali ulangan, faktor I adalah proporsi tepung terigu:tepung jagung (25:75; 50:50; 75:25)% dan faktor II adalah penembahan margarine (100; 115; 130)%.Hasil penelitian menunjukkan bahwa perlakuan terbaik adalah proporsi tepung terigu:tepung jagung (25:75)% dan penambahan margarine 130%, yang menghasilkan biskuit jagung dengan kadar air = 3,780%, kadar lemak = 37,270%, kadar serat kasar = 3,480%, tekstur = 0,666 mm/gramdetik dan uji organoleptik rasa 5,45/suka, warna 5,45/suka tekstur 5,15/agak suka.   Kata kunci : biskuit, tepung jagung, tepung gandum, margarine